Determinants of Emotion Duration and Underlying Psychological and Neural Mechanisms. (October 2015) - Verduyn, Philippe; Delaveau, Pauline; Rotgé, Jean-Yves; Fossati, Philippe; Van Mechelen, Iven
Emotions are traditionally considered to be brief states that last for seconds or a few minutes at most. However, due to pioneering theoretical work of Frijda and recent empirical studies, it has become clear that the duration of emotions is actually highly variable with durations ranging from a few seconds to several hours, or even longer. We review research on determinants of emotion duration. Three classes of determinants are identified: features related to the (a) emotion-eliciting event (event duration and event appraisal), (b) emotion itself (nature of the emotion component, nature of the emotion, and emotion intensity), and (c) emotion-experiencing person (dispositions and emotion regulatory actions). Initial evidence on the psychological and neural mechanisms that underlie their effects is discussed.